Formulasi Snack Pasta Coklat Dengan Penambahan Bubuk Carob Sebagai Subtituen - Wardhana, Danu Indra; Renandi, Berino; Setiawan, Andika Putra; Firmanto, Hendi (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2025)
Chocolate paste snack is a snack product made from cocoa powder which is in the form of a paste and does not melt at room temperature, and does not experience separation of fat and water. This product contains various additional ingredients such as vegetable oil, milk, sugar, cocoa powder, stabilizers, emulsifiers, antioxidants and additional flavors. As an alternative to conventional chocolate, Carob powder, which is low in fat and caffeine free, was chosen because it has a characteristic chocolate taste and is rich in fiber. This research aims to develop a chocolate paste snack formulation using Carob powder as a substituent for conventional chocolate. This research was conducted at the Indonesian Coffee and Cocoa Research Center and at the Agro-Industrial Processing Technology Laboratory, Muhammadiyah University of Jember from May to July 2024. The research design used a Completely Randomized Design (CRD) with four different formulations. The variables observed included organoleptic tests, water content, sugar content, fat content, and ANOVA analysis. The results showed that the test results were in accordance with SNI 7934:2014. The best sugar content test results were found in the 4th formulation with a percentage of 2.853%. The best results for the fat content test were in the first formulation with a percentage of 45%, this was due to the high amount of cocoa powder added compared to carob powder. The best water content test results were found in formulations 2 and 3 with a percentage result of 0.2%. Overall, this study provides evidence that the use of Carob powder as a chocolate substituent in chocolate paste snacks can produce products with good sensory qualities, as well as lower sugar and fat content, which is suitable for health-conscious consumers.